Epidural lumbar pneumocysts and radiculopathy: description of a clinical case of diagnosis and treatment - S. N. Larionov; A. P. Zhivotenko; A. I. Vel'm; V. A. Sorokovikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Epidural pneumocysts are a rare but significant cause of severe low back pain in patients. A clinical case of diagnosis and treatment of this disease, which often remains poorly studied in the literature, is presented. It should be noted that descriptions of nerve root compression by a gas bubble are found in both domestic and foreign publications, but they are rare, which makes the problem relevant and interesting for the medical community.